Prescription drug forms with midazolam - Anna Czech; Renata Jachowicz (Polish Pharmaceutical Society, 2021)
Midazolam is a benzodiazepine derivative. It is characterized by a short half-life. It has a strong sedative, anxiolytic and hypnotic effect. It also acts as an anticonvulsant and relaxes skeletal muscles. Due to the short half-life and quick onset of action it is used in pediatrics for sedation before anesthesia and in dentistry. The literature provides indications for midazolam in the range of 0.2 to 1 mg/kg body weight. In pediatric therapy, the oral dose should not be higher than 0.75 mg/kg. When a dose of 0.25 mg/kg is used, the risk of side effects is low, while when the maximum dose is exceeded, respiratory depression and respiratory arrest may occur. Midazolam is metabolized by the cytochrome P450 3A4 in the intestines and the liver. Inhibition of the activity of CYT450 3A4, e.g. by grapefruit juice, causes a reduced absorption of the drug in the intestines and its delayed action, as well as a reduction in the first-pass effect, which increases the concentration of midazolam in the blood. Midazolam is a weak acid with a pKa of 6,2 in water. At physiological pH midazolam is an active form, hydrophobic drug, having a weak solubility in water. Due to its lipophilic nature, it is quickly absorbed from the gastrointestinal tract and penetrates the central nervous system. It has a short effect. Injection solutions contain midazolam as hydrochloride. The solubility of midazolam hydrochloride is pH dependent and increases with decreasing value. The stability of midazolam in the pH range from 3 to 3.6 was determined. Midazolam can be administered: parenterally, orally, rectally, sublingually, nasally, and also by inhalation. There were no significant differences in bioavailability by route of administration. It is available as injection and tablets. The oral liquid form is recommended for children because of the difficulty in swallowing tablets. In absence of commercially prepared midazolam syrup Versed® or oral solution Ozalin® in some countries, injection formulation of midazolam are used for oral administration. Intravenous formulation exhibit strong bitter taste, in order to improve the acceptance by children simple syrup (Syrup BP), Syrspend® SF pH 4, Ora-Sweet®, citrus juices except grapefruit juice, HPMC are proposed as excipients to prepare a prescription drug forms from injection.